Phospholipase A2 Enzymes Regulate αIIbβ3-mediated, but not FcγRII Receptor-mediated, pp125FAK Phosphorylation in Platelets - Haimovich, Beatrice; Ji, Ping; Ginalis, Ernest; Kramer, Ruth; Greco, Ralph (Thrombosis and Haemostasis, 1999)
The αIIbβ3 integrin and FcγRII receptors mediate, respectively, platelet adhesion and spreading on fibrinogen and immunoglobulin (IgG) coated surfaces. Platelet adhesion to fibrinogen resulted in a partial conversion of the faster to the slower migrating (phosphorylated) form of Ca+2-sensitive cytosolic phospholipase A2 (cPLA2) but failed to trigger arachidonic acid (AA) release. Full mobility shift of cPLA2 and a massive release of AA release were stimulated by platelet adhesion to IgG or addition of thrombin to the fibrinogen adherent platelets. IgG and thrombin induced AA production were blocked by methyl arachidonyl fluorophosphonate (MAFP), an irreversible inhibitor of cPLA2 and the Ca+2-independent phospholipase A2 (iPLA2). In contrast, bromoenol lactone (BEL), a specific inhibitor of iPLA2 had no effect on the release of AA. MAFP and BEL prevented pp125FAK phosphorylation and platelet spreading on fibrinogen having no effect on pp125FAK phosphorylation or platelet spreading on immobilized IgG. We conclude that αIIbβ3-mediated pp125FAK phosphorylation and platelet spreading on fibrinogen are regulated by PLA2 enzymes.Abbreviations: cPLA2, cytosolic calcium-dependent phospholipase A2; iPLA2, calcium-independent phospholipase A2; BSA, bovine serum albumin; mAB, monoclonal antibody; MAFP, methyl arachidonyl fluorophosphonate; pp125FAK, focal adhesion kinase; BEL, bromoenol lactone; AA, arachidonic acid.